Plant Growth Promoting Rhizobacteria (PGPR) and Plutella xylostella (L.) (Lepidoptera: Plutellidae) interaction as a resistance inductor factor in Brassica oleracea var. capitata - Crialesi, Paula C. B. [UNESP]; Thuler, Robson T.; Iost Filho, Fernando H.; Thuler, Ana Maria G.; Lemos, Manoel V. F. [UNESP]; De Bortoli, Sergio A. [UNESP] (Horizon E-publishing Group, 2017)
Resistance of Plutella xylostella populations to chemical insecticides has made its management difficult, and the utilization of resistant cabbage cultivars has been shown to be a useful alternative. The objective of this study was to demonstrate the induction of cabbage plant resistance to P. xylostella using PGPR and injuries caused by the pest larvae as elicitors. Therefore, we evaluated the insects' responses utilizing a specific bioassay. Furthermore, this assay was used for selecting a PGPR strain that affects the insect's biology, and to examine molecular and biochemical responses of the plants influenced by the plant-microbe-insect interaction. Among the strains used in this study, Kluyvera ascorbata showed the most relevant results by influencing biological characteristics of the insect. Thus, the following tests demonstrated that the cited strain possesses a high influence on plant metabolism when it undergoes different types of stress such as injuries caused by the pest. These findings were determined from the different responses obtained by the chemical analyses of the tested plants and from the differentiation in the genetic sequences obtained from plants inoculated with or without PGPR that were injured by the pest. The PGPR K. ascorbata alters the metabolism of cabbage plants, which directs a specific plant defense against P. xylostella.
Keywords: diamondback moth; Kluyvera ascorbata; induction resistance; HPLC; sinigrin